1998
DOI: 10.1063/1.121610
|View full text |Cite
|
Sign up to set email alerts
|

Built-in voltages and asymmetric polarization switching in Pb(Zr,Ti)O3 thin film capacitors

Abstract: Asymmetric polarization switching of Pb(Zr,Ti)O3 (PZT) thin films with different electrode configuration has been studied in (La,Sr)CoO3/Pb(Zr,Ti)O3/(La,Sr)CoO3 (LSCO) heterostructures in which the conducting oxide (La,Sr)CoO3 and/or LaCoO3 (LCO) have been used as an electrode. Polarization-voltage (P-V) hysteresis loop of LSCO/PZT/LSCO was symmetric. However, LCO/PZT/LSCO showed a largely asymmetric P-V hysteresis loop and large relaxation of the remanent polarization at the negatively poled state, eventually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 14 publications
1
62
0
Order By: Relevance
“…The proposed method might therefore be even more interesting, if ferroelectric capacitors with different electrode materials will be studied. 11 Summarizing our results, the present contribution addresses the problematic of leakage current and leakage current compensation in ferroelectric thin-film capacitor structures. It is shown that an ohmic contribution in the current response of a leaky ferroelectric capacitor has a significant impact on the shape of the hysteresis curve and lead to nonphysical values of the remnant polarization and the coercive field.…”
Section: ͑3͒mentioning
confidence: 99%
“…The proposed method might therefore be even more interesting, if ferroelectric capacitors with different electrode materials will be studied. 11 Summarizing our results, the present contribution addresses the problematic of leakage current and leakage current compensation in ferroelectric thin-film capacitor structures. It is shown that an ohmic contribution in the current response of a leaky ferroelectric capacitor has a significant impact on the shape of the hysteresis curve and lead to nonphysical values of the remnant polarization and the coercive field.…”
Section: ͑3͒mentioning
confidence: 99%
“…in dynamic random access memory (DRAM), piezoelectric sensors and actuators [1,2,3,4]. For PZT thin film, the cycling stability, imprint performance and leakage current strongly depend on the used electrode material [5,6,7,8]. Electrical fatigue causes a reduction of polarization with increasing switching numbers and is a severe limitation of device operation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the PZT capacitors with noble metal electrodes like Pt exhibit a significant polarization loss when subject to bipolar switching pulses, in the past decade, for the growth of fatigue-free PZT capacitors and especially in the epitaxial form, various oxide electrodes such as La 0.5 Sr 0.5 CoO 3 (LSCO), SrRuO 3 (SRO), La 0.7 Sr 0.3 MnO 3 (LSMO), and LaNiO 3 (LNO) have been employed. [3][4][5][6][7][8]11,12 For epitaxial LSCO/PZT/LSCO capacitors, however, when exposed to reducing atmosphere for device fabrication, a large voltage offset was observed. [3][4][5] This process-induced imprint behavior was greatly complicated by the instability of the LSCO layer at reduced oxygen pressures, 5,13 and rarely examined for the other oxide electrodes.…”
mentioning
confidence: 99%
“…However, there is a lack of understanding on the formation of the internal field. Different models, such as the aligned dipolar defect complexes and asymmetric distribution of charged defects through a bulk thin film, 2-5 and a built-in electric field or a nonswitching layer at the ferroelectric-electrode interface, [6][7][8][9] have been proposed to explain the asymmetric behavior of ferroelectric capacitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation